Aerial legacies of COVID-19 - F. Klauser (Geographica Helvetica)
Based on examples taken from Switzerland, the paper offers an exploratory analysis of how the fight against COVID affected the societal relevance of the air, in its (1) elemental, (2) embodied, (3) affective, (4) socio-technical and (5) power-related dimensions. Together, these levels highlight the fact that the fight against COVID-19 increased the air's relevance as a focal point of societal concern and judgement and of competition and dispute, which in turn produced novel ways of ordering the air through legally, practically and materially defined geometries, internal structures, and contours. As the paper shows, these geometries of the air were and still are socio-politically produced in highly unequal ways. To date, they remain inherently pluralistic and as such fundamentally conflictual. The aerial legacies of COVID-19 are invested by various power relations that need critical attention. Over 150 years ago, the risks of waterborne diseases such as Cholera were tamed by the public provision of clean water. We argue that similar efforts are warranted to provide clean indoor air for all by removing the threats posed by airborne diseases such as COVID-19, influenza and tuberculosis … Our panel of scientific experts strongly recommends that the clean air needs of offices, schools, theaters, public buildings, and mass transportation systems be assessed and that measures be taken to ensure clean air in all indoor environments. (Expert group “Pandemic-proof buildings”, 2022:3)